2017
DOI: 10.1080/1478422x.2016.1271161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloride on Cu corrosion in anaerobic sulphide solutions

Abstract: The effect of chloride on copper corrosion in anaerobic aqueous sulphide solutions has been investigated using corrosion potential measurements, electrochemical impedance spectroscopy, scanning electron microscopy, focused ion beam and inductively coupled plasma atomic emission spectroscopy. Long-term exposure experiments were performed in 10 −3 mol L −1 Na 2 S solutions containing chloride concentrations in a range from 0.1 to 5 mol L −1. Chloride was found to (i) inhibit Cu 2 S film growth by displacing adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 11 publications
(22 reference statements)
4
34
0
Order By: Relevance
“…Although the location of the previously discussed base layer and its apparent thickness are indicated in Figure 8d, they are difficult to observe, owing to the presence of much larger features. The formation of such a thick crystalline outer deposit was consistent with our previous observations [ 6–15 ] and with our demonstration that growth of this deposit occurred at the film/solution interface, supported by the transport through the pores of the base layer of Cu(I), as both sulfide complexes (Cu(SH) 2 − ) and Cu 3 S 3 clusters, formed at the Cu surface. [ 15,24–29 ]…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although the location of the previously discussed base layer and its apparent thickness are indicated in Figure 8d, they are difficult to observe, owing to the presence of much larger features. The formation of such a thick crystalline outer deposit was consistent with our previous observations [ 6–15 ] and with our demonstration that growth of this deposit occurred at the film/solution interface, supported by the transport through the pores of the base layer of Cu(I), as both sulfide complexes (Cu(SH) 2 − ) and Cu 3 S 3 clusters, formed at the Cu surface. [ 15,24–29 ]…”
Section: Resultssupporting
confidence: 91%
“…Considerable effort has been expended on the investigation of the copper sulfide film formation process. [5][6][7][8][9][10][11][12][13][14][15] The physical properties of this chalcocite film have been demonstrated to vary significantly with sulfide concentration [SH − ], the flux of SH − to the Cu surface, and the presence of other groundwater anions (such as Cl − and SO 4…”
Section: Introductionmentioning
confidence: 99%
“…From the EIS spectra, the phase gradually increases and shifts towards 45°after adding Cl − . This result is due to Cl − influencing the properties of the film [103]. This phenomenon is related to the adsorption of Cl − and the reduction in the thickness of the film.…”
Section: Effect Of Chloride-ion Concentrationmentioning
confidence: 99%
“…This experimental program, which has explored effects of sulfide concentration in the presence and absence of other anions has been supported by both SKB and the NWMO and has been extensively documented in the literature. [28][29][30][31][32] The work has demonstrated that in sulfide concentrations below 30 ppm, [28] the copper sulfide films will not be protective, particularly if sulfide movement is limited by slow diffusion. Rather, the corrosion product will remain porous, such that incoming sulfide will be able to continuously react at the copper surface.…”
Section: The Anoxic Corrosion Of Copper In the Presence Of Sulfidementioning
confidence: 99%